Effect Of Cryolipolysis On Hormonal Profil And Menstrual Regularity In Obese Female With Ovarian Syndrome - Sabrin Mohamed Taha; Afaf Mohammed Mahmoud Botla; Hazem Salah El Din (2024)
Polycystic ovarian syndrome (PCOS) is a frequent disease in women that affects their ability to reproduce, their metabolism, and their ability to control their androgen levels. It is brought on by an imbalance of female sex hormones as well as is aggravated by obesity. To examine the effects of cryolipolysis on hormonal profile and menstrual regularity in obese women with PCOS.
(3eJdGReI JcjS GdeHGjV gj eQV TGFY Hjf GdSjOGJ jDKQ Ydi bOQJgf Ydi GdEfLGH, hYdi GdCjV, hYdi GdSjWQI Ydi eSJhjGJ GdCfOQhLjf(B. (3hjfJL Yf Ndd aj gQehfGJ GdLfS GdCfKhjI hjJaGbe eY GdSefI(B. (3GdgOa(B: (3aMU JCKjQ JMdd GdOghf HGdJHQjO Ydi GdgQehfGJ hGfJXGe GdOhQI GdTgQjI dOi GdSjOGJ GdHOjfGJ GdeUGHGJ HeJdGReI JcjS GdeHGjVs
Thesis (M.Sc.) -Cairo University, 2024.
Bibliography: pages 74-87.
Issued also as CD
Text in English and abstract in Arabic & English.
Keywords: Physical Therapy; Cryolipolysis -- Hormonal Profile -- Menstrual Regulation; (3JMdd GdOghf HGdJHQjOs -- (3GdgQehfGJs -- (3fXGe GdOhQI GdTgQjIs